ENHANCING MOTHERS’ COMPETENCE THROUGH EDUCATIONAL INTERVENTIONS FOR STUNTING PREVENTION IN SERANG REGENCY, BANTEN PROVINCE - Nabila Husna; Triana Indrayani; Rosmawati Lubis (International Journal of Multidisciplinary Research and Literature, 2026)
Complementary feeding practices play an important role in preventing stunting among children under two years of age. However, many mothers still have limited knowledge, attitudes, and confidence in preparing appropriate complementary foods using locally available ingredients. Educational interventions such as cooking demonstrations can help improve maternal competence in providing nutritious complementary foods. Objective: This study aimed to analyze the effect of a cooking demonstration (Demo Masak) intervention on improving mothers’ knowledge and attitudes regarding local complementary feeding (MP-ASI) practices for children aged 6–23 months. Methods: This study employed a mixed-methods, exploratory sequential design. The qualitative phase explored factors influencing maternal competence in complementary feeding practices. The quantitative phase used a quasi-experimental design with pretest, post-test 1, and post-test 2 measurements. A total of 50 mothers with children aged 6–23 months at risk of stunting were recruited as respondents. The intervention group received complementary feeding education through cooking demonstrations using locally available foods. Data were analyzed using univariate and bivariate analysis with the Chi-square test. Results: The univariate analysis showed that most respondents were aged 21–35 years (80%), had junior high school education (42%), were predominantly Sundanese (82%), and had a monthly household income of IDR 1–2 million (66%). Most respondents initially had low self-efficacy (78%) in providing complementary feeding. The intervention results showed a significant improvement in knowledge and attitudes after the cooking demonstration. The proportion of respondents with good knowledge increased from 6.7% at pretest to 100% at post-test 2. Similarly, positive attitudes increased after the intervention. The Chi-square test showed a significant relationship between the intervention and improvements in knowledge (p = 0.000) and attitudes (p = 0.005). Conclusion: Cooking demonstration-based nutrition education significantly improves mothers’ knowledge and attitudes regarding complementary feeding practices. Therefore, this interactive educational method can be recommended as an effective strategy to strengthen maternal competence in preparing local complementary foods and support stunting prevention programs.